Effects of Water Quality Adjusted by Submerged Macrophytes on the Richness of the Epiphytic Algal Community - Lv, Tian; He, Qiankun; Hong, Yaping; Liu, Chunhua; Yu, Dan (Frontiers in Plant Science, 2019)
Submerged macrophytes and epiphytic algae play significant roles in the functioning of aquatic ecosystems. Submerged macrophytes can influence the epiphytic algal community by directly or indirectly modifying environmental conditions (nutrients, light, etc.). From December to June of the following year, we investigated the occurrence dynamics of the dominant winter species Potamogeton crispus, its epiphytic algae, and water quality parameters in the shallow Liangzi Lake in China. The richness of epiphytic algae had a trend similar to that of P. crispus coverage, which increased in the first four months and then decreased in the following three months. General linear models (GLMs) indicated that the total organic carbon was the main factor explaining the variation of epiphytic algal richness (84.25% as %SS-F and 49.81% as %SS-L). The structural equation model (SEM) showed that P. crispus affected the richness of epiphytic algae by reducing nutrient concentrations (reduction in total organic carbon, total nitrogen and chemical oxygen demand) and enhancing water transparency (reduction in turbidity and total suspend solids) to enhance the richness of epiphytic algae. The results indicated that high amounts of submerged macrophyte cover can improve the richness of the epiphytic algae community by changing water quality.